A potencial consciência da ilicitude e o Povo Yanomami - Stica, Fábio Bastos (2010)
This work aims to present a different way of looking at the issue of indian s criminal problem, considering him as a human being with all mental faculties, not equalized to people with incomplete mental development, but always bearing in mind the need to recognition of their culture and traditions. Brazil recognized the indians, through Article 231 of the Federal Constitution, the right to social organization, customs, languages, beliefs and traditions. However, even today the law applicators have great difficulty in enforcing the constitutional precept, the Convention 169 of International Labour Organisation, and the infraconstitutional legislation - Statute of the Indian. The work looks for a little of the history of primitive people related to the law, especially related to the natives who were here at the time of discovery, and also approaches the dogmatic aspects of the culpability. It also brings to light practical situations involving indian peoples in conflict with Criminal Law and the attempted composition between the two cultures, respecting the traditions for the application of penalties. Finally, it presents some situations that are part of everyday life of the Yanomami, but for the Brazilian Criminal Law are considered illegal conducts, availing for that the content of the accomplished interviews of the field research